Interplay between ATRX and IDH1 mutations governs innate immune responses in diffuse gliomas - Seethalakshmi Hariharan; Benjamin T. Whitfield; Christopher J. Pirozzi; Matthew S. Waitkus; Michael C. Brown; Michelle L. Bowie; David M. Irvin; Kristen Roso; Rebecca Fuller; Janell Hostettler; Sharvari Dharmaiah; Emiley A. Gibson; et al. (Nature Communications, 2024)
Abstract Stimulating the innate immune system has been explored as a therapeutic option for the treatment of gliomas. Inactivating mutations in ATRX, defining molecular alterations in IDH-mutant astrocytomas, have been implicated in dysfunctional immune signaling. However, little is known about the interplay between ATRX loss and IDH mutation on innate immunity. To explore this, we generated ATRX-deficient glioma models in the presence and absence of the IDH1 R132H mutation. ATRX-deficient glioma cells are sensitive to dsRNA-based innate immune agonism and exhibit impaired lethality and increased T-cell infiltration in vivo. However, the presence of IDH1 R132H dampens baseline expression of key innate immune genes and cytokines in a manner restored by genetic and pharmacological IDH1R132H inhibition. IDH1R132H co-expression does not interfere with the ATRX deficiency-mediated sensitivity to dsRNA. Thus, ATRX loss primes cells for recognition of dsRNA, while IDH1R132H reversibly masks this priming. This work reveals innate immunity as a therapeutic vulnerability of astrocytomas.